ЖОҚАРЫ ОҚЫЎ ОРЫНЛАРДА ТАЛАБА ЖАСЛАРДЫҢ ЭСТЕТИКАЛЫҚ ТӘРБИЯ ПРОЦЕСИНИҢ ӘҲМИЙЕТИ - Уразимова, Т.В. (FAN va JAMIYAT, 2023)
The article is devoted to the issues of aesthetic education, the development of artistic and creative abilities of students, since in modern society attention to the problem of art education and experience has increased.